Magnetocaloric effect and tunable phase transition exponents of SrRuO 3/mica heterostructure with varied mechanical bending. (1st February 2023) - Wang, Jing; Fan, Jiyu; Liu, Fengguang; Zu, Lin; Zheng, Huan; Liu, Hao; Ma, Chunlan; Wang, Caixia; Hu, Dazhi; Zhu, Yan; Yang, Hao
Abstract: Exploitation and enhancement of the mechanical strain to modulate the magnetic properties are crucial for developing conformal wearable magnetic-electronic devices. However, the mechanical strain how to regulate the magnetic properties remains unclear for flexible thin film. Here, (111)-oriented SrRuO3 thin films are epitaxially grown on flexible mica substrates, and the influence of the mechanical bending on magnetic properties is studying by altering the curvature of the SrRuO3 /BaTiO3 /Mica heterostructure. The results show that the phase transition temperature does not reveal a significant dependence on both of convex and concave bending but they play a contrary role on the magnetic entropy change. Namely, the tensile stress (convex) increases the magnetic entropy change while the compressive stress (concave) decreases it. Moreover, based on the scale analysis method, we find that both bending states are directly correlated with the change of critical phase transition behavior. We think that the variation of domain wall configuration due to mechanical bending is the main reason for the change of magnetic properties. This study therefore not only identifies a strong magnetic property correlation in the mechanical strain, but also offers an avenue to improve flexible electronic devices with optimized performance.